2020
DOI: 10.1002/jmri.27143
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Outcome of Transcatheter Arterial Embolization Therapy for Unresectable Hepatocellular Carcinoma Based on Radiomics of Preoperative Multiparameter MRI

Abstract: Background In unresectable hepatocellular carcinoma (HCC), methods to predict patients at increased risk of progression are required. Purpose To investigate the feasibility of radiomics model in predicting early progression of unresectable HCC after transcatheter arterial chemoembolization (TACE) therapy using preoperative multiparametric magnetic resonance imaging (MP‐MRI). Study Type Retrospective. Population A total of 84 patients with BCLC B stage HCC from one medical center. According to the modified resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 38 publications
(54 reference statements)
0
42
0
Order By: Relevance
“…The value of radiomics in HCC treatment has been steadily increasing. [15][16][17][18]27 Several recent studies that combined radiomics with clinical features reported success in predicting the ORR for TACE in HCC patients. A model that combined T1WI and T2WI MRI-based radiomics with clinical features, including sex, tumor margin, peritumoral enhancement, BCLC stage, and AFP level, was generated to predict the recurrence-free survival (RFS) of HCC patients after TACE treatment, and the C-index was 0.681-0.861.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of radiomics in HCC treatment has been steadily increasing. [15][16][17][18]27 Several recent studies that combined radiomics with clinical features reported success in predicting the ORR for TACE in HCC patients. A model that combined T1WI and T2WI MRI-based radiomics with clinical features, including sex, tumor margin, peritumoral enhancement, BCLC stage, and AFP level, was generated to predict the recurrence-free survival (RFS) of HCC patients after TACE treatment, and the C-index was 0.681-0.861.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In 2020, it has been reported that ultrasound or magnetic resonance imaging (MRI) radiomics might be an effective predictor for short-term HCC prognosis after TACE. [15][16][17] Deep learning technology for CT images can also improve prediction of therapeutic response to TACE. 18 This study was the first to use a single image of non-contrast computed tomography (NC-CT) radiomics combined with features selected from clinical characteristics, laboratory data, and general CT imaging to generate a new compound model for the prediction of TACE response.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies investigated the role of radiomics at baseline imaging as predictor of response to locoregional treatment, mainly before TACE, and showed that several radiomics features (extracted from pre-treatment CT/MRI) correlated with the future response to locoregional treatment. In the recent study by Sun et al a model based on radiomics features extracted from pretreatment DWI, ADC, and T2-weighted MRI had AUC of 0.8 (p < 0.001) for prediction of progressive disease after TACE [60]. Two other studies showed correlation between pre-treatment contrast-enhanced-CT-derived texture features and mid-term (at 6 month) response to drug-eluting bead TACE [57,61].…”
Section: Assessment Of Treatment Response To Locoregional Treatmentmentioning
confidence: 99%
“…Another study with 84 HCC patients from China revealed that the model based on diffusion-weighted image features showed an AUC (b = 0, 0.786; b = 500, 0.729), followed by T2-weighted image features (0.729) and apparent diffusion coefficient images (0.714). Additionally, the radiomics signature was an independent parameter of progressive disease (PD), while clinical information had no significance in the PD group [54].…”
Section: Transcatheter Arterial Chemoembolization (Tace)mentioning
confidence: 99%